KONSEP PENDIDIKAN TAN MALAKA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Elysa Nurul Qomaria; Dita Dzata Mirrota (CENDEKIA: Jurnal Studi Keislaman, 2020)
Education in Indonesia is not yet independent because the knowledge being taught cannot free students into human beings who are socially and economically independent, instead trapped in new foedalism by pursuing degrees without actual scientific content. The Tan Malaka Education Concept states that an education based on Indonesian character, in line with reality aimed at freeing humans from misery, oppression, and ignorance, makes life more beneficial for oneself and its surroundings, there is no caste and class distinctions. While the noble goal of Islamic education is the process of making humans kaffah (perfect), which is more emphasized on the servitude of a person to his Lord, looking at the same human being seen only taqwa. This shows that Tan Malaka's thought has the same place in placing humans not as objects of education and feudalism, but also as actors in education and making people more useful to others and with quality. " Bulurejo Diwek Jombang. "